GAP ANALYSIS COMPARISON USING THE SERVQUAL MODEL FOR GO-RIDE SERVICE IN JAKARTA AND BANDUNG - Maulida, Anyssa Satharina; Rustiadi, Sonny (Journal of Business and Management, 2017)
Abstract. Initial observation capture the opinion that there is service inequality of GO-RIDE service between Jakarta and Bandung and the fierce competition between the ride-hailing applications are the trigger for the researcher to conduct a service quality measurement. The use of SERVQUAL model by Parasuraman (1985) is used to capture the customer’s expectation and perception in both cities. A questionnaire of 69 items is distributed to the respondents who have experienced the GO-RIDE service both in Jakarta and Bandung and they are asked to assessed GO-RIDE service using the 7-likert scale three times, based on their expectation in general, their perception in Jakarta, and their perception in Bandung. From 385 respondents, the average score of customer’s expectation is 5.120, and perception in Jakarta and Bandung scores 4.799 and 4.806 respectively. The average score of customer gap is -0.321 in Jakarta and -0.314 in Bandung and 0.023 for the overall gap difference. All gaps are negative except for one item per each city. But the average of the overall gap and per dimension shows negative result, thus GO-JEK still needs to improve their quality of. The biggest contributing dimension to the gap is the Tangibles. Performance Management System is needed to ensure the competences of the driver regarding the GO-RIDE service. Keywords: Customer Gap, GO-JEK, Service Quality, SERVQUAL, Informal Public Transportation